The Effect Of Service Quality, Product Quality, Price, Brand Trust, And Customer Satisfaction On Customer Loyalty: A Case Study Of Queen’s Tandoor Bali Restaurant - Widia Habeahan; Slamet Widodo (International Journal of Economics and Management, 2026)
The rapid growth of the culinary industry in the era of globalization and the digital economy has intensified competition among restaurants, requiring businesses to maintain customer loyalty through superior service and customer experience. Customer loyalty has become a crucial factor for sustaining long-term business performance, particularly in highly competitive tourism destinations such as Bali. This study examines the influence of service quality, product quality, price, brand trust, and customer satisfaction on customer loyalty at Queen’s Tandoor Bali Restaurant. The research employed a quantitative associative approach using primary data collected through questionnaires distributed to restaurant customers. A total of 90 respondents were selected using the Slovin formula and accidental sampling technique. Data analysis was conducted using multiple linear regression analysis, including validity, reliability, classical assumption, partial (t-test), simultaneous (F-test), and coefficient of determination (R²) tests. The findings revealed that service quality, product quality, price, brand trust, and customer satisfaction each had a positive and significant effect on customer loyalty. Simultaneously, all independent variables significantly influenced customer loyalty, with an F-value of 71.776 and a significance value below 0.05. The coefficient of determination (R²) value of 0.810 indicates that 81.0% of customer loyalty can be explained by the five independent variables, while the remaining 19.0% is influenced by other factors outside the study. These findings suggest that maintaining high-quality services, consistent product quality, competitive pricing, customer trust, and satisfaction are essential strategies for strengthening long-term customer loyalty in the restaurant industry